Disability grant utilization and barriers to access for patients with personality pathology: A mixed methods study - Julius, Hayley (Department of Psychiatry and Mental Health, 2024)
Background Personality disordered (PD) patients suffer the misnomer of “difficult to treat”. Difficulties in interpersonal style attendant with this diagnosis can impact on clinician attitude. This suggests that negotiating access to government health and social services, including the disability grant, might be a process with unique barriers for this group of patients. This study aims to investigate barriers that patients with PD (disorder or traits) experience in accessing the government disability grant. Methods A multi-method approach was used to identify barriers and facilitators to accessing the government disability grant in a group of psychiatric patients attending the Ward 1 therapeutic programme at Valkenberg hospital, South Africa. In the first phase, files of patients attending the programme in 2018 and 2019 were reviewed. Variables related to PD diagnosis, disability grant and others of interest were analysed using SPSS. In the second phase, purposive sampling for patients with PD and disability grant was done to conduct semi-structured interviews. Nvivo software was used to categorise and assist with analysis of themes. In the third phase an online clinician survey was conducted amongst psychiatrists and psychiatry registrars within the Department of Health, Western Cape who are tasked to assist with disability grant applications for this patient group. This was done to determine clinician beliefs and attitudes to making disability grant applications for patients with PD that may serve as barriers. Results File review: Valid data from 237 patient folders indicated that a total of 53 (22.4 %) patients had everaccess to the government disability grant (DG) and 6 (2.5 %) to private disability pay-out (Total: n = 59, 24.9 %). Half of patients admitted over the two years had a PD diagnosis (n = 122, 51.5 %). Borderline personality disorder was the most diagnosed PD (n = 68, 29 % of the sample). Although the majority of those with disability grant access had a PD diagnosis (n = 31, 52.5 %), there was no significant association between having a PD and receiving DG support. Patient interviews: Framework analysis was used to derive at 5 themes that related to Knowledge and beliefs about impairment and the disability grant, Course and access to the grant, Barriers to access, the Psychosocial impact of the disability grant, and Participant service needs related to recovery and possible sustained economic participation. Sub-theme findings related to the relationship with mental health professionals as facilitators to access, the impact of disability grant lapse on mental well-being, and three-way stigma related to having a 1) disability grant, 2) psychiatric diagnosis and 3) disability grant access for a psychiatric diagnosis. Internalised stigma was a significant finding and stigmatising judgement was experienced in interaction with general health professionals and may serve as a barrier to first access . Clinician survey: Respondent rate to the survey was low (n = 12, 21.8 %). Clinicians had much experience working with adult patients with PD, but most did not consider disability grant assessments with PD patients a routine part of their work. Confusion about how to make disability assessments for this group, compared to those with a primary common mental disorder or a serious psychiatric disorder, was salient. Most clinicians experienced dual role conflict in treating the PD patient and assessing them for a disability grant application, endorsing that the task should be delegated to another professional. Interpersonal interaction with PD patients was a challenge for clinicians but they did not believe this prevented them from considering treatment options for the patient that could support recovery and more sustained economic participation. Discussion and Recommendations: Barriers to initial access to the disability grant related to internalised stigma and patient readiness, as well as general health professional attitude. Recipients of disability grants motivated for access based on impaired functioning, in keeping with recommendations by the Department of Social Development (DSD). Functional impairment related to instability of affect, mood dysregulation that contributed to inconsistencies in behaviour, and interpersonal difficulties. These were implicated in difficulties returning to work and continuation of the disability grant. The disability grant was experienced as a significant source of support and relationships with mental health practitioners were an invaluable source of mental health support. Stigma was experienced from communities and general health professionals. The DSD mandate to routinely review access to the disability grant was a barrier contributing to distress, deterioration in mental health and socioeconomic well-being, and avoidant engagement with employment options. Recommendations to the DSD are highlighted to address realignment of the ‘temporary' grant with incentivisation for recovery and economic participation. Government multi-sectoral coordination to address stigma is highlighted. Recommendations for clinician training and practice for more confident assessment of impairment in PD patients, and to support mental health in this patient population, are made.